Algorithms and Conceptual History - Consolati, Isabella (2024)
This essay aims at contributing to the dossier dedicated to the margins of conceptual history by exploring the theoretical questions emerging from the proliferation of digitally mediated forms of social intercourse and their impact on the modern constellation of political and social concepts. It simply aims at laying out a cartography of the theoretical problems that derive from them and that need to be faced and discussed when addressing the “technological margins” of conceptual history. First it does that by looking for tools and answers in the work of the “founders” of Begriffsgeschichte, focusing in particular on how the topic of technology has been treated in laying the grounds of conceptual history. Second, it discusses some contributions that have tried to answer to the conundrums exposed above, laying the first fragments of a conceptual history of “algorithmic politics”.